Older people at risk in times of pandemic? A qualitative study of coping narratives that support resilience in older people - Pérez Sánchez, Lucía (2021)
Background: The World Health Organization mentions that the stress that COVID-19 triggers and confinement are causing a strong psychological impact on societies, due to the relationship made of the binomial pandemic and death. The above exposes the political scenario of COVID-19 for the elderly that once again exhibits the image of the elderly as fragile beings, incapable of thinking and deciding for themselves, who must be cloistered and isolated. However, despite the empirical evidence that shows a vulnerable and at-risk population in the context of the current pandemic, other theoretical views differ and emphasize the strengths that are manifested in this stage of life. Objective: To understand the narrative construction and resilient processes that the older adult population has experienced concerning COVID-19. Special attention was paid to the discourse on psycho-emotional consequences, social beliefs about old age, discrimination, as well as the omissions of human rights and dignity of the elderly. Method: qualitative descriptive cross-sectional ethnomethodological design, with a continuous inclusion sample, corresponding to 15 participants, between 64 and 85 years old, living in Mexico. Results: It was identified that the participating older adults have sufficient psycho-emotional coping resources, due to the efficacy of the regulation of the feelings experienced. However, it is still influenced by the social perception of stereotypes and stigmatization. Conclusions: The results coincide with the postulates of positive psychology and psycho-gerontology regarding the development of capacities and potentialities as a continuous process, and that in older adulthood they become present, thanks to the accumulation of experiences, individual and collective. This underlines the importance of including other ways in which old age is lived and studied, and therefore in the methodologies and proposals for intervention.